2002
DOI: 10.1002/jsfa.1151
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding regimen on apparent and true ileal nitrogen digestibility for rats fed diets containing different sources of protein

Abstract: A standard protocol is required for carrying out routine ileal nitrogen (N) digestibility rat bioassays. The aim of this study was to determine the effects of feeding regimen on ileal N digestibility in rats fed diets containing different protein sources and chromic oxide as an indigestible marker. The experimental design was seven diets (protein-free (PF), enzyme-hydrolysed casein (EHC), lactalbumin (LAC), wheat gluten (GLU), ®sh ®llets (FIS), soy protein isolate (SOY), zein) by three feeding regimens (freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…ANOVA of the isoleucine and cystine data from the four highest levels of intake showed that there was no effect of food intake over the range of 0.7 (8.0 g) to unrestricted. In a related study13 the food intakes for rats fed a variety of protein diets (lactalbumin, wheat gluten, fish fillets, soy protein isolate, zein) were in the range of 8.7–13.3 g, which indicates that, within the practical range of food intakes observed in the present feeding trial, there is no practical significance to the statistically significant slopes for the isoleucine and cystine data. Food intakes found in other studies using similar‐sized rats fed meat and bone meal diets were also found to be at the top end of and beyond the range used in the present study 25.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…ANOVA of the isoleucine and cystine data from the four highest levels of intake showed that there was no effect of food intake over the range of 0.7 (8.0 g) to unrestricted. In a related study13 the food intakes for rats fed a variety of protein diets (lactalbumin, wheat gluten, fish fillets, soy protein isolate, zein) were in the range of 8.7–13.3 g, which indicates that, within the practical range of food intakes observed in the present feeding trial, there is no practical significance to the statistically significant slopes for the isoleucine and cystine data. Food intakes found in other studies using similar‐sized rats fed meat and bone meal diets were also found to be at the top end of and beyond the range used in the present study 25.…”
Section: Discussionmentioning
confidence: 52%
“…Earlier work had shown that a meal feeding regimen was suitable for obtaining representative samples and the measurement of endogenous amino acid flows 6. 13 The procedure adopted for this study, which was based on a meal feeding regimen, was successful in obtaining a range of food dry matter intakes. At all levels of intake below 1.0 (unrestricted intake within the 3 h feeding period) the mean proportions of food dry matter eaten, compared with the amounts offered, exceeded 98%.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptions of genes related to iron absorption including divalent metal transport 1 (DMT1) and duodenal cytochrome B ferric reductase (CYBRD1) in intestinal epithelial cells were also under circadian clock regulation 15 . Several studies have found that a circadian feeding schedule could affect the circadian rhythm and improve nutrient metabolism 16‐18 . However, the contribution of circadian iron administration to circadian rhythm and iron metabolism has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%